Access Intimacy in Media Accessibility: The Audio Description of Where Memory Ends - Romero Fresco, Pablo (Journal of Audiovisual Translation, 2024)
Using my documentary Where Memory Ends (2022) as a case study, this article tracks the journey from the standard audio description offered by the production company to the alternative approach I ended up using. An initial section on standard, compliance-based access currently implemented in Spain and the UK is followed by a discussion on alternative media access viewed from the wide lens of disability justice. This section draws on disability studies to explore the notion of disability that underpins standard and alternative media access. It focuses on the discrimination suffered by disabled people in the UK during the COVID-19 pandemic, as it follows the link between participation, representation and (alternative) media access. The second part of the article presents the notion of access intimacy as it applies to the alternative audio described version of Where Memory Ends, looking at how it can be built into media accessibility research, practice and training, not as an obligation, but as a socially and politically transformative form of human connection. Lay summary Using my documentary Where Memory Ends (2022) as a case study, this article tracks the journey from the standard audio description that I was offered by the production company to the alternative approach that I ended up using. An initial section on standard, compliance-based access as currently implemented in Spain and in the UK is followed by a discussion on alternative media access viewed from the wide lens of disability justice. The focus is then placed on the notion of access intimacy and, more specifically, on how it applies to the audio description of Where Memory Ends and how it can be built into media accessibility research, practice and training.